Food and wine : the secrets of successful pairing - Haff, Harry, 1946- (McFarland & Company, Inc., Publishers, 2017)
"Knowing the factors involved in how we taste can help develop our individual palettes. This book presents a systematic approach based on personal tastes. Covering the most common international and regional wines, the author explains how they relate to the foods we eat. "Homework" assignments matching specific wines with recipes help readers learn how they taste as individuals"--